Assessment of Adherence of Public and Private Universities to Examination Regulatory Frameworks in Mount Kenya Region - Mulongo, Meshack Ambani (International Journal of Education, 2020)
The study focused on the assessment of the adherence of public and private universities to examination regulatory frameworks in Mount Kenya region.  The objectives of the study were to: assess the extent to which universities in Mount Kenya region adhere to examination regulatory frameworks, and examine the significant differences between public and private universities levels of adherence to examination regulatory frameworks in Mount Kenya region. Descriptive research design was used. The study sampled 380 university students using Kathuri and Pals’ (1999) sampling table. Self-constructed questionnaires were used to collect data from students and university examination officers and an interview schedule from registrars. Data was analyzed descriptively by use of means, percentages and frequencies; and inferentially by computation of a t-test. Results indicated that majority of universities did not adhere to regulatory frameworks as indicated by 51.3% of respondents, students were congested in examination rooms as reflected by 47.7% of subjects, and there was weakness in identification of examinees as they entered examination rooms as shown by 55.7% of respondents. The t-test yielded a p-value of 0.887 against the α value of 0.05; hence, the null hypothesis was supported (at α =.05) and concluded that the adherence to regulatory framework for private and public universities was largely the same. The study concluded that university students did not adhere to regulatory frameworks, there was no proper spacing of students in examination rooms, and there was weakness in identification of students as they entered examination rooms. The study also found that students did not borrow materials in examination rooms, and they were not allowed to talk during examinations. Implications of the study were: both public and private universities should ensure adherence to regulatory frameworks, avail sufficient spacing in examination rooms, and ensure proper identification of students as they enter examination rooms. Results will be referred to by education policy makers to improve the management of examinations in universities.